2017
DOI: 10.2147/ijn.s144452
|View full text |Cite
|
Sign up to set email alerts
|

pH-triggered surface charge-switchable polymer micelles for the co-delivery of paclitaxel/disulfiram and overcoming multidrug resistance in cancer

Abstract: Multidrug resistance (MDR) remains a major challenge for providing effective chemotherapy for many cancer patients. To address this issue, we report an intelligent polymer-based drug co-delivery system which could enhance and accelerate cellular uptake and reverse MDR. The nanodrug delivery systems were constructed by encapsulating disulfiram (DSF), a P-glyco-protein (P-gp) inhibitor, into the hydrophobic core of poly(ethylene glycol)- block -poly( l -lysine) (PEG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 49 publications
2
50
0
Order By: Relevance
“…21,39 In the spectrum of PEG-b-PLL and PEG-b-PLLZ ( Figure S2), all the peaks were consistent with the previous studies. 17,21 The degree of polymerization (DP) of lysine (Z) was calculated by comparing the signal intensities of lysine methylene protons with methylene protons of PEG, and the value was 18. 17 After deprotection, the typical peaks of carbobenzoxy groups at δ 5.0 ppm and 7.1-7.4 ppm disappeared in PEG-b-PLL, which indicated that the deprotection was complete, and the DP of lysine in PEG-b-PLL was also calculated using the same method as for PEG-b-PLLZ, and the value also was 18.…”
Section: Results and Discussion Characterization Of Peg-b-p((ll-g-ssmentioning
confidence: 99%
See 4 more Smart Citations
“…21,39 In the spectrum of PEG-b-PLL and PEG-b-PLLZ ( Figure S2), all the peaks were consistent with the previous studies. 17,21 The degree of polymerization (DP) of lysine (Z) was calculated by comparing the signal intensities of lysine methylene protons with methylene protons of PEG, and the value was 18. 17 After deprotection, the typical peaks of carbobenzoxy groups at δ 5.0 ppm and 7.1-7.4 ppm disappeared in PEG-b-PLL, which indicated that the deprotection was complete, and the DP of lysine in PEG-b-PLL was also calculated using the same method as for PEG-b-PLLZ, and the value also was 18.…”
Section: Results and Discussion Characterization Of Peg-b-p((ll-g-ssmentioning
confidence: 99%
“…The degree of substitution of DMA on PLL is 72% by calculating through the peak area of MDA and PEG. The DOX content in PEG-b-P((LLg-ss-DOX)-(LL-g-DMA)) was calculated as 11.8% (weight ratio) by comparing the peak integration of the phenyl proton of DOX with that of the PEG methylene proton signal, 17,21 and the content of DOX was measured as 9.5% by the UV spectrophotometer. 39 Because of the relative accuracy of UV spectrophotometer, we finally chose 9.5% as the content of DOX.…”
Section: Results and Discussion Characterization Of Peg-b-p((ll-g-ssmentioning
confidence: 99%
See 3 more Smart Citations